Impact of a State Concussion Law on Pediatric Emergency Department Visits. Issue 1 (January 2015) - Mackenzie, Bonnie; Vivier, Patrick; Reinert, Steven; Machan, Jason; Kelley, Caroline; Jacobs, Elizabeth
<x xml:space="preserve">Abstract</x> Objective Many states have passed concussion laws that mandate that players undergo medical clearance before returning to play. Few data have been collected on the impact of such laws on emergency department (ED) visits. This study measures the impact of Rhode Island concussion legislation on sports-related concussion visits to a pediatric ED. Methods International Classification of Diseases, Ninth Revision, Clinical Modification codes with injury mechanism–associated E-codes were extracted from hospital databases from 2004 to 2011 for both sports-related concussions and sports-related ankle ligamentous injuries (comparison group). Visit rates for sports-related concussions were compared before and after the passage of the state concussion law. Secondary outcome measures included rates of head imaging per ED visit for concussion before and after passage of the law. Times series analysis was used to analyze season-to-season count and rate changes. Results Overall rate of sports-related concussion visits more than doubled (2.2-fold increase; 95% confidence interval, 1.3–3.6; adjusted P = 0.01) during the fall sports season following the implementation of legislation (2010) relative to the previous year (3.6% vs 1.4%). Rates of sports-related ankle sprain visits tended to increase during the fall sports season but did not achieve statistical significance. Rates of computed tomography scan imaging of the head did not change over time. Conclusions The data from this study revealed an increase in pediatric ED visits for sports-related concussions, without a corresponding increase in head imaging, suggesting that the passage of a state concussion law has led to increased vigilance in evaluation of sports-related concussions, without an increase in diagnostic computed tomography scans.